NOCTUID MOTHS (LEPIDOPTERA, NOCTUIDAE, NOCTUINAE) OF COASTAL ECOSYSTEMS OF THE MIDDLE CASPIAN SEA - A. G. Abdurakhmanov (Юг России: экология, развитие, 2014)
In this article there is species staff, geographical distribution, some ecological-biological data under study.